2001
DOI: 10.1046/j.1365-4362.2001.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytomegalovirus infection in a patient with febrile ulceronecrotic Mucha‐Habermann's disease

Abstract: These results indicate that FUMHD is associated with dermal CMV manifestation. Nonetheless, the induction mechanism of FUMHD with CMV infection has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 21 publications
0
60
1
6
Order By: Relevance
“…Auster et al [4] reported positive culture of adenovirus from the urine in a 7-year-old girl with FUMHD and interstitial pneumonitis. Tsai et al [20] detected cytomegalovirus infection in the skin biopsy specimen from a 45-year-old male. Recently, Smith and Oliver [39] cultured herpes simplex type 2 from genital and a skin biopsy in 24-year-old male presenting a FUMHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auster et al [4] reported positive culture of adenovirus from the urine in a 7-year-old girl with FUMHD and interstitial pneumonitis. Tsai et al [20] detected cytomegalovirus infection in the skin biopsy specimen from a 45-year-old male. Recently, Smith and Oliver [39] cultured herpes simplex type 2 from genital and a skin biopsy in 24-year-old male presenting a FUMHD.…”
Section: Discussionmentioning
confidence: 99%
“…A febrile ulceronecrotic severe variant of PLEVA, called febrile ulceronecrotic Mucha-Habermann disease (FUMHD) is more destructive and associated to large coalescent skin necrosis with a rapid progression [1]. 48 cases of PLEVA fulminans have been reported to date in the literature with 9 lethal forms (20%) (table 1) [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. Oral, genital and conjunctival mucosa can be affected [2,6,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the disease remains obscure, but hypersensitivity reaction, possibly to an infectious agent, is suggested [2,3] . To our knowledge this is only the 2nd case of pulmonary involvement in association with this entity among the 25 cases that have been reported up to date [4][5][6][7][8] .…”
Section: A Case Of Ulceronecrotic Mucha-habermann Disease With Pulmonmentioning
confidence: 99%
“…The coexistence of vitiligo and lichen planus (LP) has rarely been observed [1][2][3] . Colocalization of these disorders is even an extremely rare situation.…”
mentioning
confidence: 99%
“…Therefore, viral immunohistology and culture should be done if the patient is at a high risk for CMV infection. For more sensitive detection of CMV reactivation, polymerase chain reaction is also recommended [21,22] . As stated previously, patients with and without GI GVHD cannot be distinguished based entirely upon clinical findings.…”
mentioning
confidence: 99%